[PP.35.21]: EFFECT OF 3-MONTH TREATMENT WITH HYPOTENSIVE DRUGS ON MINERALS AND RELATED PARAMETERS IN PATENTS WITH HYPERTENSION. (June 2015) - Musialik>, K.>; Bogdanski, P.; Galezeswka, M. Walczak; Musialik, D. Pupek
Abstract : Objective: Hypertension is an risk factor for cardiovascular disease. Prevention of cardiovascular events should be implemented in young men suffering from HT. Aim of the study was to evaluate the effect of antihypertensive treatment – ACEI – inhibitors (Ramipril) or b - blockers (Nebivolol) on biochemical parameters such as lipid profile, insulin, insulin resistance, high sensitivity C – reactive protein (hsCRP) and arterial stiffness. Design and method: The study inducted 62 patients (PTS) aged 16 – 28 years with I degree of HT, not administrating antihypertensive medicine, with excluded secondary causes of HT. Control group considered of 10 healthy volunteres. In the group 52 hypertensive separated two groups depending on antihypertensive medication. 23 PTS randomized too treatment with Nebivolol 5 mg/ day, 29 PTS receives Ramipril 5 mg/ day. In all groups evaluated anthropometric parameters (BMI, WHR – waist/hip Ratio). Determined laboratory test – serum insulin, insulin resistance using HOMA Index. In all PTS evaluated arterial stiffness index (SI) using photoplethyzmozmography method. Serum insulin determined method Elisa. In the group 52 hypertensive investigated the same was repeated after 3 months of therapy. Results: In the group with Ramipril therapy was observed significant reduction of hsCRP. We observed in Ramipril group serum insuline decreased was 5 time, reduction of the HOMA Index was two times. Higher than in the Nebivolol group. Conclusions: 2) Ramipril has beneficial effect on biochemical parameters significant increase HDL, lowering blood glucose and hsCRP concentration. We observed insignificant trend of decling insulin level and insulin resistance. Nebivolol treatment shows no such metabolic benefits. 3) Both analyzed drugs have different effect on arterial stiffness index. ECEI therapy leads to the significant decrease in SI, B – blockers does not affect the value of SI. This may suggest beneficial role of ACEI.